Brief Motivational Interventions for College Student Drinking May Not Be as Powerful as We Think: An Individual Participant‐Level Data Meta‐Analysis. (May 2015) - Huh, David; Mun, Eun‐Young; Larimer, Mary E.; White, Helene R.; Ray, Anne E.; Rhew, Isaac C.; Kim, Su‐Young; Jiao, Yang; Atkins, David C.
<x xml:space="preserve">Abstract</x> Background For over 2 decades, brief motivational interventions (BMIs) have been implemented on college campuses to reduce heavy drinking and related negative consequences. Such interventions include in‐person motivational interviews (MIs), often incorporating personalized feedback (PF), and stand‐alone PF interventions delivered via mail, computer, or the Web. Both narrative and meta‐analytic reviews using aggregate data from published studies suggest at least short‐term efficacy of BMIs, although overall effect sizes have been small. Methods This study was an individual participant‐level data (IPD) meta‐analysis of 17 randomized clinical trials evaluating BMIs. Unlike typical meta‐analysis based on summary data, IPD meta‐analysis allows for an analysis that correctly accommodates the sampling, sample characteristics, and distributions of the pooled data. In particular, highly skewed distributions with many zeroes are typical for drinking outcomes, but have not been adequately accounted for in existing studies. Data are from Project INTEGRATE, one of the largest IPD meta‐analysis projects to date in alcohol intervention research, representing 6, 713 individuals each with 2 to 5 repeated measures up to 12 months postbaseline. Results We used Bayesian multilevel over dispersed Poisson hurdle models to estimate intervention effects on drinks per week and peak drinking, and Gaussian models for alcohol problems. Estimates of overall intervention effects were very small and not statistically significant for any of the outcomes. We further conducted post hoc comparisons of 3 intervention types (individual MI with PF, PF only, and group MI) versus control. There was a small, statistically significant reduction in alcohol problems among participants who received an individual MI with PF. Short‐term and long‐term results were similar. Conclusions This study questions the efficacy and magnitude of effects of BMIs for college drinking prevention and intervention and suggests a need for the development of more effective intervention strategies.